2022
DOI: 10.3389/fpls.2022.894398
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Inter-Annual Variations of Carbon Dioxide Fluxes and Their Determinants in an Alpine Meadow

Abstract: The alpine meadow is one of the most important ecosystems on the Qinghai-Tibet Plateau (QTP) due to its huge carbon storage and wide distribution. Evaluating the carbon fluxes in alpine meadow ecosystems is crucial to understand the dynamics of carbon storage in high-altitude areas. Here, we investigated the carbon fluxes at seasonal and inter-annual timescales based on 5 years of observations of eddy covariance fluxes in the Zoige alpine meadow on the eastern Tibetan Plateau. We found that the Zoige alpine me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…While it is likely that GPP would change, it was not possible to determine by how much. The range in GPP measured for intact Zoige peatland studies was 590-2054 g C m 2 year À1 (Hao et al, 2011;Liu, Zhu, et al, 2019;Yao et al, 2022), while other studies from alpine meadows (which can represent a successional stage of peatland degradation), showed a similarly large range (Wang et al, 2016(Wang et al, , 2022. One study of degradation in alpine meadows suggested that in the initial stages, that is, (0%-20% degradation) GPP may increase in accordance with increased vegetation biomass, but this then declined as degradation increased (Yang et al, 2022).…”
Section: Effects Of Land Management On Necbmentioning
confidence: 95%
See 1 more Smart Citation
“…While it is likely that GPP would change, it was not possible to determine by how much. The range in GPP measured for intact Zoige peatland studies was 590-2054 g C m 2 year À1 (Hao et al, 2011;Liu, Zhu, et al, 2019;Yao et al, 2022), while other studies from alpine meadows (which can represent a successional stage of peatland degradation), showed a similarly large range (Wang et al, 2016(Wang et al, , 2022. One study of degradation in alpine meadows suggested that in the initial stages, that is, (0%-20% degradation) GPP may increase in accordance with increased vegetation biomass, but this then declined as degradation increased (Yang et al, 2022).…”
Section: Effects Of Land Management On Necbmentioning
confidence: 95%
“…Degradation impacts on decomposition rates and exchange of greenhouse gases due to a lowering of the water table, while warming may cause similar effects (Hopple et al, 2020; Ma et al, 2022). Indeed, degradation caused by land‐use and climate change may lead to a weakening the Zoige peatland C sink function (Wang et al, 2022). Numerous experimental studies have been conducted on the effects of land management and climate change on aspects of the Zoige peatland C cycle (Cao et al, 2017; Yang et al, 2014; Yang et al, 2017; Zhou et al, 2021), however, there have been no reviews of the Zoige peatland C cycle to date.…”
Section: Introductionmentioning
confidence: 99%